Ruhul Ma’had Compass: Integrating Spirituality and Scientific Excellence in Pesantren Mahasiswa Al-Hikam Malang - Moh. Nadhif; Mamluatu Solihah; Umi Nahril Ula; Rodifatul Chasanah; A. Samsul Ma'arif (Academicus: Journal of Teaching and Learning, 2026)
Through an exploration of how value-centered frameworks could thoroughly influence student development in an Islamic boarding school context, the present study aims to address the ongoing disconnect between spiritual values and academic achievement in the realm of higher education settings. The purpose is to conceptualize and statistically examine the Ruhul Ma'had Compass as a paradigm of unifying spiritual values and student development in Pesantren Mahasiswa Al-Hikam Malang. Utilizing the qualitative case study method of data collection, in which in-depth interviews, participant observation, and document analysis are employed in conjunction with a theoretical application of spirituality theories, micro-foundational theories, and value-based education theories to uncover the underlying processes of value assimilation, the results of the present study indicate that Ruhul Ma'had serves as an ethical and intellectual guidance system in which the cognitive frameworks of the student are methodically imbued with essential values such as honesty, integrity, simplicity, respect, and independence, thereby informing student academic and life processes. Moreover, the Pesantren Mahasiswa Al-Hikam Malang slogan of amaliah agama, prestasi ilmiah, and kesiapan hidup is reinterpreted from an essentially symbolic perspective to an instrumental model of unifying moral, intellectual, and practical competencies. The study reveals that Ruhul Ma'had Compass provides a unique micro-level theory of understanding the application of spirituality in higher education, which places pesantren as a relevant global example of value-integrated educational systems that go beyond the traditional dichotomy of the study of religion and scientific exploration.